Does Compensation & Benefits Matters to Working Women to Perform Well? A Case of Public School Teachers - Saif, Amir; Amir, Maira; Hussain, Fawad (Journal of Education and Vocational Research, 2019)
Pakistan is a developing country and with the changing global trend, technological advancement and human development are taking place. As we know that training and development is a constant growing process which keeps improving the excellence of employees. In education sector training, development and continuous learning play an important role. Teachers spend their lives grooming our children, youth and shaping our generations. Education is the key element for the success of any society. But unfortunately, there are various reasons why the quality of learning and competency level in the Public sector is not up to the benchmark both for students and teachers in Pakistan. According to report 2015-16 of Pakistan education institution of statistics the total primary schools is 145829 of 145, in which is 125573 is public primary school. On the other hand, as per education statistics there are a total of 422,797 primary school teachers of which 324,561 (77%) represents the public sector With such a huge contribution of public schools, there is a great room of improvement for teacher particularly their educational capability to deliver, then only a gradual change can be seen in the long run. The aim of the study is investigating the relationship between training and development, work engagement and women public teachers’ performance. This study also examines compensation & benefits as a moderating variable. This study has used a total of 220 samples to analyze the data. The study has used Smart PLS and SPSS 22 statistical technique to analyze the data. This study used a quantitative method, in which data collected from working women (public school teachers) in Multan, Lodhran, Khanewal, and Vehari cities of the province Punjab in Pakistan. The findings have concluded that there is a significant relationship between training & development, work engagement and employee performance. However, compensation & benefits do not found to be a moderating variable. This research will be helpful for women public teacher’s related issue to training, work engagement, compensation, and benefits. The study recommends this problem could be resolved by considering some basic measures such as appropriate government policy for public teachers training and development, foolproof accountability system, education quality assessment. Injecting latest talent in the education system, international competitive pay scale, and merit-based transparent hiring process and believe that only education can change our children’s future.